GENDER DIFFERENCES IN CONSECUTIVE PARTICIPATION IN ARTISTIC GYMNASTICS AT THE OLYMPIC GAMES FROM 1996 TO 2016 - Sunčica Delaš Kalinski; Almir Atiković; Igor Jelaska (Science of Gymnastics Journal)
The main goal of a gymnast’s career is participation in the Olympic Games (OG) at least once. Survey results determined a significant difference between genders in the number of gymnasts who competed in only one OG (277 males and 408 females); also, between those who consecutively participated in two OG (104 males and 70 females), three OG (28 males and 11 females), and four OG (six males and zero females). There were no gender differences found in the number of those who consecutively participated in five OG (one male and one female) and six OG (zero males and one female). For both genders, for consecutive participants of three and more OG longevity of high-quality performance, seen through their rank in different finals, was presented showing how it is not endangered with their above average age. The obtained results should be the encouragement for the coaches to plan quality training for more than one Olympic cycle during which the constant increase in the quality of the performance, for both genders, can and should be expected.